Epigallocatechin Gallate During Dietary Restriction — Potential Mechanisms of Enhanced Liver Injury - Shi, Zhuo; Zhu, Jing-xiao; Guo, Yu-ming; Niu, Ming; Zhang, Le; Tu, Can; Huang, Ying; Li, Peng-yan; Zhao, Xu; Zhang, Zi-teng; Bai, Zhao-fang; Zhang, Guang-qin; et al. (Frontiers in Pharmacology, 2021)
Green tea extract (GTE) is popular in weight loss and the epigallocatechin gallate (EGCG) is considered as the main active component. However, GTE is the primary cause of herbal and dietary supplement-induced liver injury in the United States. Whether there is a greater risk of liver injury when EGCG is consumed during dieting for weight loss, has not been previously reported. This study found for the first time that EGCG could induce enhanced lipid metabolism pathways, suggesting that EGCG had the so-called "fat burning" effect, although EGCG did not cause liver injury at doses of 400 mg/kg or 800 mg/kg in normal mice. Intriguingly, we found that EGCG caused dose-dependent hepatotoxicity on mice under dietary restriction, suggesting the potential synergy between dietary restriction and EGCG. The synergy between EGCG and dietary restriction led to over-activation of linoleic acid and arachidonic acid oxidation pathways, significantly increasing the accumulation of pro-inflammatory lipid metabolites, and thus mediating liver injury. We also found that the disruption of Lands’ cycle and sphingomyelin-ceramides cycle as well as the high expression of taurine-conjugated bile acids were important metabolomic characteristics in EGCG-induced liver injury under dietary restriction. This original discovery suggests that people should not go on a diet while consuming EGCG for weight loss, otherwise the risk of liver injury will be significantly increased. This discovery provides new evidence for understanding the "drug-host" interaction hypothesis of drug hepatotoxicity and provides experimental reference for clinical safe use of green tea-related dietary supplements.